Analysis of Contextual Problem Solving Ability of Three-Variable Linear Equation System Material Given Mathematical Disposition - Ismiranda, Khoirina; Nurcahyo, Adi; Utami, Nida Sri (Universitas Wiralodra, 2024)
This research aims to analyze students' difficulties related to mathematical dispositions and measure students' abilities in solving problems related to three-variable linear equation systems based on mathematical dispositions. Descriptive analysis methods are used in this qualitative research. All X-G students were given a mathematical disposition survey as part of the data collection process for this research. Three students were selected from each mathematical disposition category to take a test of their contextual problem-solving skills. Based on the results of the research, there were three groups of students in class X-G SMAN 1 TOROH, namely 3 students with high mathematics dispositions, 14 students with medium mathematics dispositions, and 16 students with low mathematics dispositions. Based on the analysis of answers and discussions, students with strong mathematical skills have excellent problem-solving skills because they meet three problem-solving indicators, namely making a problem-solving plan, implementing a problem-solving plan, and evaluating problems. Students have difficulty in the indicator of understanding problems because they are not used to writing what they know and what is asked. Students with a moderate mathematical disposition meet two indicators of problem-solving, namely creating and implementing a problem-solving plan, so they are in the moderate category in terms of problem-solving. Students with moderate mathematical dispositions also have difficulty writing the conclusion of the problem. Because students with low mathematical dispositions only fulfill one indicator, namely evaluating the problem, these students have problem-solving skills in the low category. In addition, students with low mathematical dispositions had difficulty in applying the formula.